Mesenchymal stem cells combined with traditional Chinese medicine (qi‐fang‐bi‐min‐tang) alleviates rodent allergic rhinitis. Issue 2 (18th September 2019) - Fu, Yanxia; Kong, Yanhua; Li, Jun; Wang, Yi; Li, Mengdi; Wang, Ying; Wang, Yinyin; Ren, Fangli; Ni, Jian; Li, Youlin; Chang, Zhijie
Abstract: Mesenchymal stem cells (MSCs) have been proved to exert anti‐inflammatory effects and regulate immune reactions. Traditional Chinese medicine (TCM), qi‐fang‐bi‐min‐tang, is effective for some patients with allergic diseases. However, it remains unclear whether MSCs combined with TCM could benefit the treatment of allergic rhinitis (AR). In this study, we reported an additional effect of TCM (qi‐fang‐bi‐min‐tang) on the therapy of AR under MSCs treatment. Intriguingly, we observed that TCM‐treated MSCs significantly inhibited the symptoms of AR and reduced the pathological changes of nasal mucosa in ovalbumin (OVA)‐induced rats. The expression levels of interferon γ (IFN‐γ), interleukin‐17 (IL‐17), and IL‐4 were significantly decreased in the plasma of AR rats after injection of TCM‐treated MSCs. TCM‐treated MSCs reduced the levels of histamine secreted by mast cells and immunoglobulin E (IgE) secreted by plasma cells. In addition, we found that MSCs combined with TCM had a better therapeutic effect than TCM alone on AR in an OVA‐induced mouse model. After OVA induction, MSCs combined with TCM significantly reduced the ratio of T helper type 1 (Th1), Th2, and Th17, but increased the proportion of Treg in the spleen of mice. Consistently, the expression levels of IFN‐γ, IL‐4, and IL‐17 were significantly decreased, but transforming growth factor‐β1 was significantly increased in the plasma of AR mice after treated with TCM and MSCs. Our results from both rats and mice indicated that the effects of TCM combined with MSCs on the AR might be through regulating the secretion of Th1, Th2, and Th17 cytokines. This study suggested that TCM (qi‐fang‐bi‐min‐tang)‐treated MSCs could be used in the clinical therapy of AR. Abstract : Allergen exposure at mucosal surfaces results in T helper type 1 (Th1), Th2, and Th17 differentiation. Th2 cells play an essential role in the production of cytokines, such as interleukin‐4 (IL‐4), which are responsible for the induction of mast cells, basophil, and eosinophil activity. Furthermore, Th2 cells drive B‐cells to produce allergen‐specific immunoglobulin E (IgE). The differentiation of Th1 cells accompanied by an increase of interferon γ (IFN‐γ), which also promotes B‐cells to produce allergen‐specific IgE and aggravates allergic rhinitis (AR). In addition, the differentiation of Th17 cells accompanied by an increase of IL‐17, which aggravates AR. Traditional Chinese medicine (TCM)‐treated MSCs significantly reduced the levels of IFN‐γ and IL‐17. Our study indicated that TCM‐treated MSCs alleviates AR by inhibiting the secretion of IFN‐γ and IL‐17 by Th1 and Th17 cells.